PENGARUH PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. PEGADAIAN (PERSERO) KANWIL II PEKANBARU - M. Arip; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to find out and analyze training and work discipline and its effect on employee performance at PT. Pegadaian (Persero) Kanwil II Pekanbaru. Trainingas a variable (X1), work discipline as a variable (X2), and Employee Performance as a variable (Y). The method used in this study is descriptive and quantitative using the SPSS 21 program, where the sample used is 87 employees conducted by simple random sampling and data collection techniques through questionnaires. The results of the analysis use the validity test, reliability test, determination test, simple linear regression test, multiple linear regression test, t test and F test. So that it can be concluded that traininghas a significant effect on the performance of employees of PT. Pegadaian (Persero) Kanwil II Pekanbaru, work discipline has a significant effect on employee performance at PT. Pegadaian (Persero) Kanwil II Pekanbaru, and training and work discipline have a significant effect on the performance of PT. Pegadaian (Persero) Kanwil II Pekanbaru.Keywords: Training, Work Discipline and Employee Performance